Central incisor restoration (Case Report) - Alessandro Conti (LLC "Endo Press", 2021)
This case report describes the 11 tooth old restoration removal and new direct composite restoration placement(Enamel Plus, Micerium S.p.A, Avengo, Ge, Italy). Direct anterior restorations are today a very nice, minimal invasive and cheap opportunity to restore one or more teeth. With the use of modern materials, the right techniques and protocols we can obtain mimetic restorations that they can work on the mouth of the patient for a long time.